ETHNO-MATHEMATICS EXPLORATION ON THE CARVINGS OF RUMAH GADANG IN SOUTH SOLOK REGENCY OF WEST SUMATERA - *, Fauziah; *, Niniwati (IJRDO- Journal of Educational Research, 2017)
This study aimed to analyze ethno-mathematic exploration for basic information in the development of ethno-mathematics. The method of this research was by doing interview through questionnaire; and the data processed by taxonomic analysis. Taxonomic analysis done to create a category of cultural symbols that exist in the culture studied. The object of research was the shape and the name of carvings in Rumah Gadang. From the data analysis, the result obtained that most of Rumah Gadang in South Solok Regency has carved of 44.44%. There were 34 of carvings in Rumah Gadang and mostly symmetric to 76.47%.